Review of Thermosyphon Applications - Wagner, Anna M (2014)
Thermosyphons have been used for stabilizing permafrost since 1960. The original thermopile was designed as a vertical unit with one end buried in the ground and the other end exposed to the air. More recently, flat, loop, and buried thermosyphons have been developed. Thermosyphons consist of a pipe or series of pipes that are installed with one part below ground (evaporator) and the other exposed to the air (condenser). They are filled with a pressurized fluid that evaporates because of the heat of the soil and rises as a vapor to the condenser. If the air temperature is lower than that of the soil, the vapor will condense on the inside walls of the pipe and release the transported heat from the ground to the air. The condensate then returns to the evaporator by gravity. When the air temperature is higher than that of the soil, the heat transfer ceases and the unit is dormant. Presented here is a general overview of applications of thermosyphons in cold regions. The original document contains color images.